2005
DOI: 10.2139/ssrn.843505
|View full text |Cite
|
Sign up to set email alerts
|

Oil Prices, Inflation and Interest Rates in a Structural Cointegrated VAR Model for the G-7 Countries

Abstract: SummarySharp increases in the price of oil are generally seen as a major contributor to business cycle asymmetries. Moreover, the very recent highs registered in the world oil market are causing concern about possible slowdowns in the economic performance of the most developed countries. While several authors have considered the direct channels of transmission of energy price increases, other authors have argued that the economic downturns arose from the monetary policy response to the inflation presumably cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 78 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…However, previous studies have revealed that the linkage between oil price shocks and stock market performance is not completely linear and that positive oil price shocks (i.e. price decrease) tends to have smaller impact on growth when compared to negative (Cologni and Manera, 2005;Atems and Lame, 2015;Olagbaju and Akinbobola, 2016). The transmission mechanism of oil price shocks to Nigeria stock market returns are ambiguous and the broad effect of oil price shocks on stock returns depends on which of the negative (domestic and imported inflation) or positive (effects of oil prices increase on Nigerian economy) effects offset the other.…”
Section: Introductionmentioning
confidence: 96%
“…However, previous studies have revealed that the linkage between oil price shocks and stock market performance is not completely linear and that positive oil price shocks (i.e. price decrease) tends to have smaller impact on growth when compared to negative (Cologni and Manera, 2005;Atems and Lame, 2015;Olagbaju and Akinbobola, 2016). The transmission mechanism of oil price shocks to Nigeria stock market returns are ambiguous and the broad effect of oil price shocks on stock returns depends on which of the negative (domestic and imported inflation) or positive (effects of oil prices increase on Nigerian economy) effects offset the other.…”
Section: Introductionmentioning
confidence: 96%